The Role of Local Governments in Increasing Pond Yield Case ( Study Of A Farmer’s Group in North Sinjai Spectacle, Sinjai Regency) - Fahruddin Fahruddin; Sulmiah Sulmiah (Universitas Negeri Makassar, 2022)
This study aims to determine the description of the role of local government in increasing the yield of farmer groups in North Sinjai Sub-district, Sinjai Regency. This type of research is descriptive qualitative research with data collection techniques, namely interviews, observation, and documentation. The checking of the validity of the data is done through triangulation of sources. Data analysis techniques using data condensation, data presentation, and drawing conclusions. The results of this study indicate that the role of the local government in increasing the yield of farmer groups in North Sinjai District, Sinjai Regency is going well, although there are still several indicators that need to be considered, namely social and economic conditions. The target of the Government's policy is the community towards the results of the fishpond. The resources used are human resources and equipment resources. The characteristics of the implementing organization are the Regional Government, the Fisheries Service in charge of managing the management of pond products, and the Farmer Group as recipients of the results of the pond. The Extension Coordinator as the executor of confirmation of the results of aquaculture to the farmer groups in Sinjai Regency shows good support from the implementors, the form of support provided is to provide services that are responsive to the community regarding the results of ponds. The social, economic, and political environment of the community still has not received well the policies issued by the Regional Government due to the different economic levels of the community.Keywords: Implementation, Legislation, Ranperda